Mixed casting nylon sleeper and preparation process thereof

Through mixed cast nylon sleepers and their preparation process, the problems of high weight and poor environmental protection of traditional sleepers are solved, and the lightweight, durability and environmental protection of sleepers are achieved, reducing maintenance costs and noise, improving service life and comfortable riding sex.

CN119391175AInactive Publication Date: 2025-02-07HUAIAN DONGCHI ELECTROMECHANICAL PARTS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411822776.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing rail transit sleeper materials have problems such as environmental protection, heavy weight, difficulty in installation, high maintenance costs and high noise, and are difficult to meet the needs of modern rail transit to be high-speed, safe, lightweight and environmentally friendly.

Method used

Using mixed cast nylon sleepers and their preparation process, casting caprolactam as the main material with sodium hydroxide, toluene diacecyanate, glass fiber powder, nanotitanium dioxide and other auxiliary materials in a specific proportion, combining extrusion molding, heat treatment and ultraviolet Photocuring and other processes have been used to prepare sleepers with high mechanical properties, weather resistance and self-cleaning properties.

Benefits of technology

It realizes the lightweight, durability and environmental protection of the sleepers, reduces the phenomenon of ballast powdering and maintenance costs, improves the service life and ride comfort of the track, and has efficient self-cleaning capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391175A_ABST
    Figure CN119391175A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rail transit infrastructure, in particular to a mixed casting nylon sleeper and a preparation process thereof, the mixed casting nylon sleeper is formed by mixed casting of a main material and an auxiliary material according to the mass percentage, the auxiliary materials comprise sodium hydroxide, toluene diisocynate, glass fiber powder, glass beads, peregal, polyethylene glycol, a PVT liquid flexibilizer, sodium carbonate, silicone grease or silicone oil, toner, molybdenum disulfide and newly added nano titanium dioxide; by adopting the glass fiber powder and other reinforcing materials, the high tensile strength and impact resistance of the product are ensured, and the service life of the track is prolonged. Compared with the prior art, the railway ballast pulverization phenomenon is reduced, nano titanium dioxide is introduced and is matched with ultraviolet curing treatment, surface cleanness can be maintained, pollutant attachment is reduced, the maintenance difficulty is reduced, compared with a traditional concrete sleeper, the weight of the product is reduced by 50%-70%, and the installation and transportation cost and the labor intensity are greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of rail transit infrastructure, and in particular to a mixed-cast nylon sleeper and a preparation process thereof. Background Art

[0002] With the rapid development of modern rail transit, the demand for sleepers not only requires them to have good mechanical properties and durability, but also emphasizes environmental protection, lightweight, shock absorption and noise reduction. Although the traditional wooden sleepers and reinforced concrete sleepers have played an important role in history, they have many disadvantages: wooden sleepers are not environmentally friendly and easy to corrode; reinforced concrete sleepers have problems such as heavy weight, difficult installation, high maintenance cost, and high noise. In addition, these materials seem to be unable to cope with the development trend of modern railways towards high speed, safety, lightweight and environmental protection.

[0003] In recent years, the research and application of composite sleepers have gradually emerged, aiming to overcome the shortcomings of traditional materials. For example, Patent No. 201410604820.1 discloses a hollow composite sleeper prepared by an impregnation resin system, which uses a vinyl resin combined with glass fiber roving to achieve good mechanical properties. However, the sleepers prepared by this method still have some limitations, such as high process complexity, low production efficiency, and unstable performance under certain environmental conditions.

[0004] On the other hand, Patent No. 201510826475.0 introduces a composite material sleeper consisting of a sleeper body and a sleeper core, which improves the overall performance of the product to a certain extent by optimizing the material ratio and structural design. However, the production process of this type of sleeper is also relatively complicated, and the application effect in special environments (such as extreme temperature changes) still needs to be improved.

[0005] Therefore, the development of a new type of mixed cast nylon sleeper and its preparation process has become an urgent problem to be solved in the current rail transportation field. This sleeper should be able to take into account the advantages of concrete sleepers and wooden sleepers, while responding to new development trends and meeting the needs of modern rail transportation industry. Summary of the invention

[0006] In view of the above, it is necessary to provide a mixed cast nylon sleeper and a preparation process thereof.

[0007] The present application provides a mixed-cast nylon sleeper and a preparation process thereof, which is formed by mixing and casting a main material and an auxiliary material according to a mass percentage, wherein the main material is caprolactam; Auxiliary materials include sodium hydroxide, toluene diacetate, glass fiber powder, glass microspheres, perchlorate, polyethylene glycol, PVT liquid toughener, sodium silicate, silicone grease or silicone oil, color powder, molybdenum disulfide, and newly added nano titanium dioxide (TiO2) to enhance weather resistance and self-cleaning properties; The mass percentages of the raw materials are as follows: sodium hydroxide 0.1-0.15%, toluene diacetylide 0.8-1.2%, glass fiber powder 6-8%, glass microbeads 4-6%, perigax 2-3%, polyethylene glycol 2-3%, PVT liquid toughening agent 3-4%, sodium sulfate 2-3%, silicone grease or silicone oil 1-2%, color powder 0.5-1%, molybdenum disulfide 2-3%, nano titanium dioxide 0.5-1.5%, and caprolactam 61.65%-72.6%.

[0008] In a possible implementation, the nano titanium dioxide is used to improve the weather resistance of the product, increase the hydrophobicity and self-cleaning effect of the surface, reduce the attachment of pollutants, and reduce maintenance costs.

[0009] The present invention also protects a preparation process of a mixed cast nylon sleeper, comprising the following steps: The first step is to place each raw material in a container, preheat it to 155-160°C and vacuum dehydrate it for 5-10 minutes; Step 2: Add auxiliary materials according to mass percentage at 150°C and stir evenly; The third step is to add the main material into the pretreated auxiliary material according to the mass percentage and stir evenly; Step 4: Put the mixture into a mold preheated to 155-160°C to melt; Step 5: 5-10 minutes after the mixture is completely melted, start the 500-ton press to extrude and shape; Step 6: After 5-10 minutes of extrusion and shaping, the rough product is removed from the mold; In the seventh step, the crude product is sent to a 500-ton press for extrusion for 4-6 minutes to prevent deformation. The applied pressure range is 480-520 tons, and the temperature is controlled between 157-160°C to ensure the compactness and dimensional stability of the internal structure of the sleeper. Step 8: heat-treating the crude product after anti-deformation treatment in 150°C water for 24 hours; The ninth step is to use a CNC lathe to finish the rough product after heat treatment; The tenth step is to use UV light source to irradiate the surface of the sleeper to complete the curing, so that the nano-titanium dioxide activates its photocatalytic activity, thereby further enhancing the self-cleaning performance and weather resistance of the sleeper; Step 11: Complete product inspection, packaging acceptance and warehousing.

[0010] In a possible implementation, in the first step, each raw material is preheated to 155° C. and vacuum-dehydrated for 10 minutes, while ensuring that the nano-titanium dioxide is fully dispersed.

[0011] In a possible implementation, in the second step, auxiliary materials are put into a container according to mass percentage and stirred evenly at a temperature of 150° C., with particular attention paid to the uniform distribution of nano-titanium dioxide.

[0012] In a possible implementation, in the third step, the main material is added to the pretreated auxiliary material according to the mass percentage and fully stirred to ensure that the nano titanium dioxide is well combined with other ingredients.

[0013] In a possible implementation, in the fifth step, a 500-ton press is started 10 minutes after the mixture in the mold is completely melted to perform extrusion shaping, during which the nano-titanium dioxide is kept in a stable state.

[0014] In a possible implementation, in the eleventh step, a protective layer with photocatalytic activity is formed on the surface of the sleeper through a UV light curing step, which effectively enhances the self-cleaning ability and weather resistance of the sleeper.

[0015] In a possible implementation, in the second step, the polyethylene glycol in the auxiliary material is selected to have a molecular weight of 400-600 to optimize the fluidity of the mixture and improve the surface finish of the final product.

[0016] In one possible implementation, in the UV curing step, the wavelength of the UV light source is selected to be around 365 nm, and the irradiation time is 15-30 minutes, to ensure that the nano-titanium dioxide layer achieves optimal photocatalytic activity while avoiding thermal damage to the material.

[0017] In the above-mentioned mixed-cast nylon sleeper and its preparation process, glass fiber powder and other reinforcing materials are used to ensure the high tensile strength and impact resistance of the product, and extend the service life of the track. The ballast powdering phenomenon is reduced, and the track maintenance cost is reduced; at the same time, due to the weather resistance and anti-aging properties of the material itself, the daily maintenance workload is further reduced. The introduction of nano-titanium dioxide and the combination of ultraviolet light curing treatment give the product efficient self-cleaning ability and lasting photocatalytic activity, which helps to maintain surface cleanliness, reduce the adhesion of pollutants, and reduce the difficulty of maintenance.

[0018] Compared with traditional concrete sleepers, the weight of the product of the present invention is reduced by 50%-70%, which greatly reduces the cost and labor intensity of installation and transportation. The product exhibits excellent bending strength (≥150MPa) and shear strength (≥120MPa), maintains good track gauge performance, effectively reduces wheel rolling noise and vibration, and improves ride comfort.

[0019] The present invention has the characteristics of low thermal expansion coefficient and low thermal conductivity, and can work stably for a long time under adverse weather conditions; and has excellent corrosion resistance, UV resistance, aging resistance, insulation and heat resistance, ensuring the safety and smooth operation of the train.

[0020] The product of the present invention can be recycled and reused for a second time, which is in line with the concept of green development and reduces environmental pollution. The service life is expected to be 40-50 years, far exceeding that of wooden sleepers and reinforced concrete sleepers, greatly reducing the replacement frequency and related costs. By accurately controlling the parameters in each step, such as preheating temperature, stirring time and pressure, an efficient and stable production process is achieved, ensuring the consistency and reliability of product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0022] Figure 1 This is a mixed-cast nylon sleeper and a process flow chart of its preparation in one embodiment of the present application. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0024] Example 1 See also Figure 1 This embodiment provides a technical solution: a mixed cast nylon sleeper and a preparation process thereof, comprising the following steps: Material ratio: Sodium hydroxide: 0.1%; toluene diacetylide: 0.8%; glass fiber powder: 6%; glass microspheres: 4%; perchlorate: 2%; polyethylene glycol (molecular weight 400): 2%; PVT liquid toughener: 3%; sodium sulfate: 2%; silicone grease: 1%; color powder: 0.5%; molybdenum disulfide: 2%; nano titanium dioxide: 1%; caprolactam: 76.6%.

[0025] Preparation process: Preheating and dehydration: Place each raw material in a stainless steel container, preheat it to 155°C on an electric heating plate, and use a vacuum pump to evacuate to -0.09MPa and maintain for 10 minutes to remove moisture.

[0026] Mixing of auxiliary materials: Add auxiliary materials according to mass percentage at 150°C and use a high-speed stirrer (speed of 1200rpm) to stir evenly for 30 minutes to ensure that nano titanium dioxide and other auxiliary materials are fully dispersed.

[0027] Addition of main ingredients: gradually add the main ingredient caprolactam into the pretreated auxiliary materials. After each addition, use a low-speed mixer (speed of 300 rpm) to fully stir for 5 minutes to ensure that all ingredients are evenly dispersed.

[0028] Mold melting: The evenly stirred mixture is put into a mold preheated to 155°C. The mold is pre-coated with a layer of silicone oil as a release agent to prevent sticking.

[0029] Extrusion shaping: 10 minutes after the mixture in the mold is completely melted, start the 500-ton press for extrusion shaping. The pressure is maintained at 500 tons and the temperature is controlled at 160°C for 10 minutes.

[0030] After extrusion and shaping, cool the mold to room temperature and carefully take out the rough product to avoid damaging the product surface.

[0031] Anti-deformation re-extrusion: The crude product enters a 500-ton press and is extruded for another 6 minutes to prevent deformation. During this period, the pressure is maintained at 500 tons and the temperature is controlled at 157°C.

[0032] Heat treatment: The rough product after anti-deformation is placed in a special hot water tank with the water temperature maintained at 150℃ for 24 hours to optimize the internal structure and physical properties.

[0033] Finishing: Use CNC lathes to accurately cut and grind the rough products after heat treatment to ensure that the dimensional accuracy meets the railway industry standards, and use precision measuring equipment to detect.

[0034] Inspection and warehousing: Complete product inspection, check appearance quality, dimensional accuracy and other indicators, and put into storage after packaging acceptance.

[0035] UV curing: Use a UV light source (wavelength 365nm) to irradiate the sleeper surface for 20 minutes to activate the photocatalytic activity of the nano-titanium dioxide layer and enhance its self-cleaning ability and weather resistance.

[0036] The performance test results are as follows: Bending strength: ≥150MPa; Shear strength: ≥120MPa; Water absorption: <0.5%; Corrosion resistance: Excellent, passed the salt spray test; Self-cleaning effect: significantly better than products without adding nano titanium dioxide.

[0037] Example 2 This embodiment provides a technical solution: a mixed cast nylon sleeper and a preparation process thereof, comprising the following steps: Material ratio: Sodium hydroxide: 0.125%; toluene diacetylide: 1.0%; glass fiber powder: 7%; glass microspheres: 5%; perchlorate: 2.5%; polyethylene glycol (molecular weight 500): 2.5%; PVT liquid toughener: 3.5%; sodium sulfate: 2.5%; silicone oil: 1.5%; color powder: 0.75%; molybdenum disulfide: 2.5%; nano titanium dioxide: 1%; caprolactam: 71.125%.

[0038] Preparation process: Preheating and dehydration: Place each raw material in a stainless steel container, preheat it to 155°C on an electric heating plate, and use a vacuum pump to evacuate to -0.09MPa and maintain it for 10 minutes to remove moisture.

[0039] Mixing of auxiliary materials: Add auxiliary materials according to mass percentage at 150°C and use a high-speed stirrer (speed of 1200rpm) to stir evenly for 30 minutes to ensure that nano titanium dioxide and other auxiliary materials are fully dispersed.

[0040] Addition of main ingredients: gradually add the main ingredient caprolactam into the pretreated auxiliary materials. After each addition, use a low-speed mixer (300 rpm) to stir thoroughly for 5 minutes to ensure that all ingredients are evenly dispersed.

[0041] Mold melting: The evenly stirred mixture is put into a mold preheated to 155°C. The mold is pre-coated with a layer of silicone oil as a release agent to prevent sticking.

[0042] Extrusion shaping: 10 minutes after the mixture in the mold is completely melted, start the 500-ton press for extrusion shaping. The pressure is maintained at 500 tons and the temperature is controlled at 160°C for 10 minutes.

[0043] After extrusion and shaping, cool the mold to room temperature and carefully take out the rough product to avoid damaging the product surface.

[0044] Anti-deformation re-extrusion: The crude product enters a 500-ton press and is extruded for another 6 minutes to prevent deformation. During this period, the pressure is maintained at 500 tons and the temperature is controlled at 157°C.

[0045] Heat treatment: The rough product after anti-deformation is placed in a special hot water tank with the water temperature maintained at 150℃ for 24 hours to optimize the internal structure and physical properties.

[0046] Finishing: Use CNC lathes to accurately cut and grind the rough products after heat treatment to ensure that the dimensional accuracy meets the railway industry standards, and use precision measuring equipment to detect.

[0047] Inspection and warehousing: Complete product inspection, check appearance quality, dimensional accuracy and other indicators, and put into storage after packaging acceptance.

[0048] UV curing: Use a UV light source (wavelength 365nm) to irradiate the sleeper surface for 20 minutes to activate the photocatalytic activity of the nano-titanium dioxide layer and enhance its self-cleaning ability and weather resistance.

[0049] In this embodiment, the polyethylene glycol is selected to have a molecular weight of 500, and the other parameters remain unchanged. As the molecular weight of the polyethylene glycol increases, the fluidity of the mixture is slightly improved, and the surface finish of the finished product is also improved.

[0050] Performance test results: Bending strength: ≥155MPa; Shear strength: ≥125MPa; Water absorption: <0.4%; Corrosion resistance: excellent, passed the salt spray test; Surface finish: high, better than Example 1.

[0051] Example 3 This embodiment provides a technical solution: a mixed cast nylon sleeper and a preparation process thereof, comprising the following steps: Material ratio: Sodium hydroxide: 0.15%; toluene diacetylide: 1.2%; glass fiber powder: 8%; glass microspheres: 6%; perchlorate: 3%; polyethylene glycol (molecular weight 600): 3%; PVT liquid toughening agent: 4%; sodium hydroxide: 3%; silicone grease: 2%; color powder: 1%; molybdenum disulfide: 3%; nano titanium dioxide: 1.5%; caprolactam: 65.65%.

[0052] Preparation process: Preheating and dehydration: Place each raw material in a stainless steel container, preheat it to 155°C on an electric heating plate, and use a vacuum pump to evacuate to -0.09MPa and maintain it for 10 minutes to remove moisture.

[0053] Mixing of auxiliary materials: Add auxiliary materials according to mass percentage at 150°C and use a high-speed stirrer (speed of 1200rpm) to stir evenly for 30 minutes to ensure that nano titanium dioxide and other auxiliary materials are fully dispersed.

[0054] Addition of main ingredients: gradually add the main ingredient caprolactam into the pretreated auxiliary materials. After each addition, use a low-speed mixer (speed of 300 rpm) to fully stir for 5 minutes to ensure that all ingredients are evenly dispersed.

[0055] Mold melting: The evenly stirred mixture is put into a mold preheated to 155°C. The mold is pre-coated with a layer of silicone oil as a release agent to prevent sticking.

[0056] Extrusion shaping: 10 minutes after the mixture in the mold is completely melted, start the 500-ton press for extrusion shaping. The pressure is maintained at 500 tons and the temperature is controlled at 160°C for 10 minutes.

[0057] After extrusion and shaping, cool the mold to room temperature and carefully take out the rough product to avoid damaging the product surface.

[0058] Anti-deformation re-extrusion: The crude product enters a 500-ton press and is extruded for another 6 minutes to prevent deformation. During this period, the pressure is maintained at 500 tons and the temperature is controlled at 157°C.

[0059] Heat treatment: The rough product after anti-deformation is placed in a special hot water tank with the water temperature maintained at 150℃ for 24 hours to optimize the internal structure and physical properties.

[0060] Finishing: Use CNC lathes to accurately cut and grind the rough products after heat treatment to ensure that the dimensional accuracy meets the railway industry standards, and use precision measuring equipment to detect.

[0061] Inspection and warehousing: Complete product inspection, check appearance quality, dimensional accuracy and other indicators, and put into storage after packaging acceptance.

[0062] UV curing: Use a UV light source (wavelength 365nm) to irradiate the sleeper surface for 30 minutes to activate the photocatalytic activity of the nano-titanium dioxide layer and enhance its self-cleaning ability and weather resistance.

[0063] The higher molecular weight polyethylene glycol in this embodiment further enhances the fluidity of the mixture and the surface finish of the finished product, while the extended UV curing time makes the photocatalytic activity of the nano-titanium dioxide layer more stable.

[0064] Performance test results: Bending strength: ≥160MPa; Shear strength: ≥130MPa; Water absorption: <0.3%; Corrosion resistance: excellent, passed the salt spray test; Photocatalytic activity: high, good long-term stability.

[0065] Example 4 This embodiment provides a technical solution: a mixed cast nylon sleeper and a preparation process thereof, comprising the following steps: Material ratio: Sodium hydroxide: 0.1%; toluene diacetylide: 1.2%; glass fiber powder: 8%; glass microspheres: 6%; perchlorate: 3%; polyethylene glycol (molecular weight 600): 3%; PVT liquid toughening agent: 4%; sodium hydroxide: 3%; silicone grease: 2%; color powder: 1%; molybdenum disulfide: 3%; nano titanium dioxide: 0.5%; caprolactam: 68.6%.

[0066] Preparation process: Preheating and dehydration: Place each raw material in a stainless steel container, preheat it to 155°C on an electric heating plate, and use a vacuum pump to evacuate to -0.09MPa and maintain for 10 minutes to remove moisture.

[0067] Mixing of auxiliary materials: Add auxiliary materials according to mass percentage at 150°C and use a high-speed stirrer (speed of 1200rpm) to stir evenly for 30 minutes to ensure that nano titanium dioxide and other auxiliary materials are fully dispersed.

[0068] Addition of main ingredients: gradually add the main ingredient caprolactam into the pretreated auxiliary materials. After each addition, use a low-speed mixer (speed of 300 rpm) to fully stir for 5 minutes to ensure that all ingredients are evenly dispersed.

[0069] Mold melting: The evenly stirred mixture is put into a mold preheated to 155°C. The mold is pre-coated with a layer of silicone oil as a release agent to prevent sticking.

[0070] Extrusion shaping: 10 minutes after the mixture in the mold is completely melted, start the 500-ton press for extrusion shaping. The pressure is maintained at 500 tons and the temperature is controlled at 160°C for 10 minutes.

[0071] After extrusion and shaping, cool the mold to room temperature and carefully take out the rough product to avoid damaging the product surface.

[0072] Anti-deformation re-extrusion: The crude product enters a 500-ton press and is extruded for another 6 minutes to prevent deformation. During this period, the pressure is maintained at 500 tons and the temperature is controlled at 157°C.

[0073] Heat treatment: The rough product after anti-deformation is placed in a special hot water tank with the water temperature maintained at 150℃ for 24 hours to optimize the internal structure and physical properties.

[0074] Finishing: Use CNC lathes to accurately cut and grind the rough products after heat treatment to ensure that the dimensional accuracy meets the railway industry standards, and use precision measuring equipment to detect.

[0075] Inspection and warehousing: Complete product inspection, check appearance quality, dimensional accuracy and other indicators, and put into storage after packaging acceptance.

[0076] UV curing: Use a UV light source (wavelength 365nm) to irradiate the sleeper surface for 20 minutes to activate the photocatalytic activity of the nano-titanium dioxide layer and enhance its self-cleaning ability and weather resistance.

[0077] In this embodiment, the mass percentage of nano titanium dioxide is 0.5%, and the other parameters remain unchanged. The lower nano titanium dioxide content slightly reduces the self-cleaning effect, but still provides a certain degree of weather resistance and surface smoothness.

[0078] Performance test results: Bending strength: ≥158MPa; Shear strength: ≥128MPa; Water absorption: <0.4%; Corrosion resistance: good, close to Example 3; Self-cleaning effect: good, but not as good as Example 3.

[0079] Comparative Example 1 Material ratio: Same as Example 1, but without adding nano titanium dioxide.

[0080] Preparation process: Except for omitting the nano titanium dioxide and the corresponding ultraviolet light curing step, the rest of the preparation process is the same as Example 1. Without the participation of nano titanium dioxide, the self-cleaning effect of the product is significantly reduced, and the surface smoothness is not as good as the product containing nano titanium dioxide.

[0081] Performance test results: Bending strength: ≥145MPa; Shear strength: ≥115MPa; Water absorption: <0.6%; Corrosion resistance: good, but not as good as Example 1; Self-cleaning effect: poor, easy to accumulate stains.

[0082] Comparative Example 2 Material ratio: Same as Example 1, but the mass percentage of glass fiber powder is reduced to 4%, while the mass percentage of caprolactam is increased to 78.6%.

[0083] Preparation process: Same as Example 1, but in the seventh step of re-extrusion of the crude product, only 450 tons of pressure was applied and the temperature was controlled at 155° C. Due to the reduction of glass fiber powder content, the mechanical strength and wear resistance of the product decreased; the lower pressure and temperature resulted in insufficient density of the crude product, affecting the dimensional stability and mechanical properties of the final product.

[0084] Performance test results: Bending strength: ≥130MPa; Shear strength: ≥105MPa; Water absorption: <0.7%; Corrosion resistance: General, failed to pass the strict salt spray test; Dimensional stability: Poor, prone to deformation.

[0085] The test results according to the above embodiments and comparative examples are as follows: Serial number project Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 1 Bending strength (MPa) ≥150 ≥155 ≥160 ≥158 ≥145 ≥130 2 Shear strength (MPa) ≥120 ≥125 ≥130 ≥128 ≥115 ≥105 3 Water absorption (%) <0.5 <0.4 <0.3 <0.4 <0.6 <0.7 In this document, the directional words such as front, back, top, and bottom are defined by the positions of the components in the drawings and the positions of the components relative to each other, and are only for the sake of clarity and convenience in expressing the technical solution. It should be understood that the use of the directional words should not limit the scope of protection claimed in this application.

[0086] Obviously, the embodiments described above are only part of the embodiments of the present application, rather than all of the embodiments. The present application is not limited to the details of the above embodiments, and any appropriate changes or modifications made by ordinary technicians in the relevant technical field are deemed to be within the patent scope of the present application.

Claims

1. A mixed cast nylon sleeper, characterized in that: It is made by mixing and casting the main material and the auxiliary material according to the mass percentage, wherein the main material is caprolactam; Auxiliary materials include sodium hydroxide, toluene diacetate, glass fiber powder, glass microspheres, perchlorate, polyethylene glycol, PVT liquid toughener, sodium silicate, silicone grease or silicone oil, color powder, molybdenum disulfide, and newly added nano titanium dioxide (TiO2) to enhance weather resistance and self-cleaning properties; The mass percentages of the raw materials are as follows: sodium hydroxide 0.1-0.15%, toluene diacetylide 0.8-1.2%, glass fiber powder 6-8%, glass microbeads 4-6%, perigax 2-3%, polyethylene glycol 2-3%, PVT liquid toughening agent 3-4%, sodium sulfate 2-3%, silicone grease or silicone oil 1-2%, color powder 0.5-1%, molybdenum disulfide 2-3%, nano titanium dioxide 0.5-1.5%, and caprolactam 61.65%-72.6%.

2. A mixed cast nylon sleeper according to claim 1, characterized in that: The nano titanium dioxide is used to improve the weather resistance of the product and increase the hydrophobicity and self-cleaning effect of the surface.

3. The preparation process of a mixed cast nylon sleeper according to claim 1, characterized in that: The following steps are involved: The first step is to place each raw material in a container, preheat it to 155-160°C and vacuum dehydrate it for 5-10 minutes; Step 2: Add auxiliary materials according to mass percentage at 150°C and stir evenly; The third step is to add the main material into the pretreated auxiliary material according to the mass percentage and stir evenly; Step 4: Put the mixture into a mold preheated to 155-160°C to melt; Step 5: 5-10 minutes after the mixture is completely melted, start the 500-ton press to extrude and shape; Step 6: After 5-10 minutes of extrusion and shaping, the rough product is removed from the mold; In the seventh step, the crude product is sent to a 500-ton press for extrusion for 4-6 minutes to prevent deformation. The applied pressure range is 480-520 tons, and the temperature is controlled between 157-160°C to ensure the compactness and dimensional stability of the internal structure of the sleeper. Step 8: heat-treating the crude product after anti-deformation treatment in 150°C water for 24 hours; The ninth step is to use a CNC lathe to finish the rough product after heat treatment; The tenth step is to use a UV light source to irradiate the surface of the sleeper to complete the curing, so that the nano-titanium dioxide activates its photocatalytic activity; Step 11: Complete product inspection, packaging acceptance and warehousing.

4. The preparation process of a mixed cast nylon sleeper according to claim 3, characterized in that: In the first step, the raw materials were preheated to 155°C and vacuum-dehydrated for 10 minutes while ensuring that the nano-titanium dioxide was fully dispersed.

5. The preparation process of a mixed cast nylon sleeper according to claim 3, characterized in that: In the second step, the auxiliary materials were put into the container according to the mass percentage and uniformly stirred at a temperature of 150°C.

6. The process for preparing a mixed cast nylon sleeper according to claim 3, characterized in that: In the third step, the main material is added to the pretreated auxiliary material according to the mass percentage and fully stirred to ensure that the nano titanium dioxide is well combined with other ingredients.

7. The process for preparing a mixed-cast nylon sleeper according to claim 3, characterized in that: In the fifth step, 10 minutes after the mixture in the mold is completely melted, the 500-ton press is started for extrusion and shaping, during which the nano-titanium dioxide is kept in a stable state.

8. The process for preparing a mixed-cast nylon sleeper according to claim 3, characterized in that: In the eleventh step, a protective layer with photocatalytic activity is formed on the surface of the sleeper through a UV light curing step, which effectively enhances the self-cleaning ability and weather resistance of the sleeper.

9. The process for preparing a mixed cast nylon sleeper according to claim 3, characterized in that: In the second step, the polyethylene glycol in the excipient is selected with a molecular weight of 400-600 to optimize the fluidity of the mixture and improve the surface finish of the final product.

10. The process for preparing a mixed cast nylon sleeper according to claim 3, characterized in that: In the UV curing step, the wavelength of the UV light source is selected to be around 365 nm, and the irradiation time is 15-30 minutes.

Citation Information

Patent Citations

  • Composite sleeper

    CN105332324A

  • Preparation method of composite material sleeper

    CN105619843A